DEVELOPMENT OF URBAN TOURISM IN THE LARGEST HISTORICAL CENTERS OF THE WORLD - KHUDAVERDIYEVA, Victoriya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article presents the main theoretical approaches to urban tourism, defines the etymology of the definitions of "urban tourism" and "urban travel", gives the main motives for visiting the largest cities - world tourist centers by travelers, analyzes the key indicators of urban tourism, presented in the rankings of world leaders - the research group "Mastercard", as well as a group of researchers from the research center European Urban Marketing. The paper presents the main indicators of attendance of world cities by tourists, income received by cities - world and European tourist centers. The purpose of the article is to analyze the features of tourism development in the largest historical cities of the world. The essence of urban tourism is established, an analysis of the features of the development of urban tourism in the largest historical cities of the world is carried out, the main tourist resources of the cities of the world are analyzed, the features of the specific component of urban tourism are revealed, and the formation of a rating of the leading urban tourist centers is proposed. The methodological basis of the study is the foundations of scientific dialectics. The main research methods are comparative geographical, statistical, descriptive, point (rating) assessment, analytical, literary. The scientific novelty lies in the analysis of the perceptual perception of the world's largest historical cities through the eyes of tourists. This study is an important component of organizing a perceptual-tourist analysis of the largest historical cities in the world. Its results contribute to the development of individual components of the tourist cognitive perception of an urbanized territory, the activation of the processes of spiritual-mental, economic-organizational and socio-social convergence of modularly crushed functionally and structurally isolated urban areas among themselves.
Keywords: city tourism; rating; destination attractiveness; financial income; European city marketing; Mastercard rating; Euromonitor International